My detachment : a memoir - Kidder, Tracy (New York : Random House, 2005)
The author presents realistic day-to-day reports on his mission in Vietnam which included daily reports on enemy troop movements and commanding a small detachment of men.
Adult
Adult
Library Journal
Booklist starred
Publisher's Weekly
Keywords: Vietnam War, 1961-1975 -- Personal narratives, American; Kidder, Tracy; Vietnam War, 1961-1975 -- Personal narratives; Kidder, Tracy